Tinjauan Hukum Pidana Islam dalam Putusan Nomor 316/Pid.B/2024/PN NNK Tentang Sanksi Tindak Pidana Pembunuhan Berencana: An Overview of Islamic Criminal Law in Decision Number 316/Pid.B/2024/PN NNK Concerning the Sanction for the Crime of Premeditated Murder - Mustakim, Merang; Saepullah, Usep; Sumardi, Didi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze the judge’s legal considerations in Decision Number 316/Pid.B/2024/PN Nnk regarding the criminal act of premeditated murder and to examine its relevance to Islamic criminal law. The research employs a normative legal approach through a library research method. Data were obtained from primary legal materials such as the Indonesian Penal Code (KUHP) and court decisions, as well as secondary legal materials including Islamic legal literature and fiqh jinayah. The analysis was conducted qualitatively using case, comparative, and conceptual approaches to connect the norms of positive law and Islamic law with the existing legal facts. The results show that the panel of judges found the elements of intent and premeditation in the case of Bahdaniar alias Emi binti Muhammad Idris to be proven, thereby imposing a fourteen-year prison sentence. From the perspective of Islamic criminal law, the act is categorized as qatl al-‘amd (intentional homicide), which carries sanctions of qishas, diyat, or afw, emphasizing both retributive and restorative justice. Substantively, the decision reflects the protection of the human right to life (ḥifẓ al-nafs), although it has not yet fully accommodated the social and spiritual dimensions of justice as outlined in Islamic law.